Over the fence - Monroe, Mary (Monroe, Mary. Neighbors, 2019)
Bootlegging was Milton and Yvonne Hamilton<U+2019>s ticket out of poverty, prison time, and plain bad luck. Now they<U+2019>ve moved on to a bigger, richer pool of clientele right in their own respectable, new middle-class backyard. And their growing friendship with the seemingly perfect couple Joyce and Odell Watson is proving golden in more ways than one . . . As Milton soon learns, Odell is hiding an outside family and dubious business dealings. It<U+2019>s the perfect recipe for a blackmail scheme that will help Milton hide his own dirty secrets- even from Yvonne. Better yet, he can take ever more dangerous risks to ace out his liquor-smuggling rivals. And Yvonne, emboldened by her husband<U+2019>s new gravy train, delights in tormenting Joyce about everything the snobbish matron doesn<U+2019>t have, especially children. But even a winning hand can be played too far. Pushed past their limits, Odell and Joyce will play on Milton<U+2019>s careless boasting to get him and Yvonne out of their lives for good . . .